Central Eurasia in global politics : conflict, security, and development - Amineh, Mehdi Parvizi; Houweling, Henk (International studies in sociology and social anthropology ;, 2005)
This anthology brings together studies of post-colonial, post-Cold War Central Eurasia. This part of the world is in transition from Soviet institutions to independent statehood, nation building, resistance against state expansion, cultural change and the release of market forces. The theoretical framework of the study is called 'critical geo-politics.' The objective of the work is to better comprehend the nature of the post-colonial 'Great Game'. Part I studies US power projection activity in the region. America is extending its World War II transoceanic 'defense perimeter into the fossile fuel rich area between integrating Europe, recovering Russia and industrializing China. Part II details various aspects of state-nation building and soci-cultural and economic change in the region. Part III studies interactions between outsiders, neighbors and Central Asian Republics. Conflict and cooperation in the Caspian region is studied in part IV, with Aral Sea and Azerbijan as cases.